2021
DOI: 10.1111/iwj.13550
|View full text |Cite
|
Sign up to set email alerts
|

Virulent and multidrug‐resistant Klebsiella pneumoniae from clinical samples in Balochistan

Abstract: Klebsiella pneumoniae is an important pathogen causing hospital-acquired infections in human beings. Samples from suspected patients of K pneumoniae associated with respiratory and urinary tract infections were collected at Bolan Medical Complex, Quetta, Balochistan. Clinical samples (n = 107) of urine and sputum were collected and processed for K pneumoniae isolation using selective culture media. Initially, 30 of 107 isolates resembling Klebsiella spp. were processed for biochemical profiling and molecular d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 41 publications
5
11
0
Order By: Relevance
“…In contrast, yersiniabactin eludes binding to Lcn2, thereby avoiding the inflammatory response and promoting bacterial growth ( Lam et al., 2018 ). As expected, we found the entB gene in all the strains tested in agreement with another study ( Fatima et al., 2021 ). Besides, the higher prevalence of the siderophore-encoded ybtS and fyuA genes in the respiratory tract isolates compared to the urinary and blood strains confirmed that yersiniabactin is an important virulence factor for the pulmonary infection, as reported by previous studies ( Yan et al., 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, yersiniabactin eludes binding to Lcn2, thereby avoiding the inflammatory response and promoting bacterial growth ( Lam et al., 2018 ). As expected, we found the entB gene in all the strains tested in agreement with another study ( Fatima et al., 2021 ). Besides, the higher prevalence of the siderophore-encoded ybtS and fyuA genes in the respiratory tract isolates compared to the urinary and blood strains confirmed that yersiniabactin is an important virulence factor for the pulmonary infection, as reported by previous studies ( Yan et al., 2016 ).…”
Section: Discussionsupporting
confidence: 93%
“…The present study was found a low prevalence of K. pneumoniae (27.8%) in total included clinical samples. The result was in consistent with 19.6% and 24% as estimated respectively, via [21] along with [22] and seems to be lower than that reported by [23] in clinical samples, who reported a frequency % of K. pneumoniae positivity is 73.3%.…”
Section: Discussionsupporting
confidence: 87%
“…In a 2021 study by Fatima et al[ 24 ], among SXT-resistant strains, the frequency of sulI (66.7%) gene was similar to our study (60.9%). Although all of the tetracycline-resistant strains had the tetB gene, in our study only there was 12.6% of tetB gene that could indicate other mechanisms in the development of tetracycline resistance in bacteria.…”
Section: Main Textsupporting
confidence: 90%